Grandmother as a Narrator in Raja Rao’s Kanthapura – A Critique (Literary Voice, 2023)
For any literary work, the narrative technique constitutes one of the essential requisites. How the art of narration is chiseled in a literary work is what lends it artistic and emotional credibility. In Kanthapura, Raja Rao experiments with the narrative technique. The novel is presented from the viewpoint of an old grandmother who relates the tale of the brave resistance of the people of Kanthapura to expel the British from India. The ancient Indian Puranic method has been preferred to the western narrative technique, which according to Raja Rao, suits the Indian credo and climate. In Kanthapura, Raja Rao sought to defamiliarize the English language by bringing to the standard English form Indian thought and feeling, Indian culture, and Indian ideology. The present paper essays to investigate how Raja Rao used different elements and structures in narrating Kanthapura as experimenting tools to lend the novel a lasting artistic quality that served the purpose he had in mind. The reliability of the narrator in her description and narration of incidents and characters will be under scrutiny.
Keywords: Narrator, Defamiliarization, Reliability, Authenticity, Patriarchy, Kanthapura